EXTRACTION OF KETAPANG SEEDS (TERMINALIA CATAPPA LINN) AS RAW MATERIAL OF BIODIESEL - Putri, Novy Pralisa; Muslim, Muhammad Affandhy; Sitorus, Joel Gerystra; Putra, Dicky Luhangga; Marjenah, Marjenah (Universitas Lambung Mangkurat, 2018)
Abstract- Terminalia catappa Linn. (ketapang) is a coastal tree with a widespread area. Its derived from the tropics of India, and spread to Southeast Asia, Northern Australia and Polynesia in the Pacific Ocean. This study aims to determine the effect of maceration time on the density of the species, yield, and % FFA from oil of ketapang. The research procedure is done by soaking ketapang seed powder wrapped with filter paper into a chemical glass containing 500 mL of n-Hexane solvent. Then the solvent which has been mixed with oil, separated by distillation. Variables used in this research is the variation of immersion time in the unit of day. The results of the research are 25-31 mL of oil volume, yield percentage of 0.44-0.52, density of 0.84-0.88 g / mL, 28-35% percentage of FFA. Ketapang oil obtained a lot of fatty acids that can be used as raw materials for making biodiesel but it needs to be pre-esterification first to reduce levels of FFA up to 2%. Keywords: FFA, Ketapang Oil, Maseration, Yield